"You've broken the patient": Physiotherapists' lived experience of incivility within the healthcare team - An Interpretative Phenomenological Analysis. (December 2022) - Naylor, Michelle J.; Boyes, Christopher; Killingback, Clare
Abstract: Background: Incivility in healthcare teams is a widely recognised phenomenon. The impact of incivility is far-reaching with consequences for healthcare organisations, individuals and patient care. To date there has been little research into the effects of incivility on physiotherapists, with the extant literature focussed on nurses and physicians. Purpose: To explore the impact of incivility on physiotherapists working in the acute hospital setting Methods: A qualitative design using Interpretative Phenomenological Analysis was used. Semi-structured interviews were conducted with a group of physiotherapists (n = 6). Analysis: The transcripts were analysed using six-step analysis common to interpretative phenomenological analysis. Member checking was used to enhance the quality of the study. Results: Two superordinate themes were identified. Superordinate theme one, impact of incivility on the professional self and superordinate theme two, impact of incivility on the emotional self were identified as novel. Conclusion and Implications: The impact of incivility on physiotherapists, professionally and personally, should not be underestimated and further qualitative and quantitative research is required to identify and implement strategies which may mitigate the effects on individuals and the profession as whole. Contribution of the Paper: Key messages . Incivility has a negative impact on physiotherapists, professionally and personally. Physiotherapy services would benefit from a greater understanding of the concept and impact of incivility on clinicians to improve the wellbeing of staff. What the paper adds . Novel understanding of physiotherapists' lived experience of incivility. A base from which to further explore the concept of incivility and its relation to physiotherapy practice. New Knowledge Incivility exists within physiotherapy teams and should be acknowledged and addressed. Physiotherapists perceptions of incivility echo those of existing research into the impact of incivility within healthcare.